RHETORIC ANALYSIS ON STAND UP COMEDY - Nuzulul Fitri Yolandari (Jurnal Bahasa Lingua Scientia, 2021)
This kind of discourse has some specific characteristics in terms of its creation and language use. A qualitative study was conducted with the data source from stand-up comedy records. The data were reduced to obtain the funniest humor discourse. Furthermore, the data were analyzed based on the creation technique and the construction elements of humor discourse in terms of linguistic and non-linguistic context. The research findings showed that the creation technique and the construction elements of stand-up comedy humor discourse in local perspective in Indonesia were in line with the general concepts and theories of humor discourse creation techniques namely: (a) rhetoric, (b) tone variation, (c) irony, (d) language misunderstanding, (e) wordplay, (f) verbal jokes, (g) sarcasm, (h) satire, (i) sexual satire, and (j) deception. In addition, the results confirmed that the most widely used of creation techniques were rhetoric, wordplay, and deception. The three techniques are more pronounced than other techniques due to the local comics circumscribed public speaking capability.